Methods And Algorithms For Identification And Control Of Non-Stationary Dynamic Objects - Sotvoldiev Khusniddin (Academia One Publishing, 2023)
identification algorithms have been developed for large non-stationary objects, various methods for describing non-stationary dreiffs have been considered. The resulting algorithms, in general, are of a convergent nature, but are considered to be exact for linear dreyfian laws. Although these algorithms are not strictly justified and are not estimates of the approach speed, numerical examples testify to the fact that the proposed algorithms are performance-capable and efficient. This article scientifically investigated the methods and algorithms for identifying and manipulating non-stationary dynamic objects
Keywords: algorithms; dynamic object; identification; application